Preliminaries to the Study of Morality and Law - Znamierowski, Czesław (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Rozważania wstępne do nauki o moralności i prawie by Czesław Znamierowski published originally in Polish by PWN Publishing House in 1966. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.